General practitioners' deprescribing decisions in older adults with polypharmacy: a case vignette study in 31 countries - Jungo, Katharina Tabea; Mantelli, Sophie; Rozsnyai, Zsofia; Missiou, Aristea; Biljana Gerasimovska Kitanovska; Weltermann, Birgitta; Mallen, Christian; Collins, Claire; Bonfim, Daiana; Kurpas, Donata; Petrazzuoli, Ferdinando; Dumitra, Gindrovel; et al. (Springer Science and Business Media LLC, 2021)
General practitioners (GPs) should regularly review patients' medications and, if necessary, deprescribe, as inappropriate polypharmacy may harm patients' health. However, deprescribing can be challenging for physicians. This study investigates GPs' deprescribing decisions in 31 countries.